SQSTM1/p62 activates NFE2L2/NRF2 via ULK1-mediated autophagic KEAP1 degradation and protects mouse liver from lipotoxicity. Issue 11 (1st November 2020) - Lee, Da Hyun; Park, Jeong Su; Lee, Yu Seol; Han, Jisu; Lee, Dong-Kyu; Kwon, Sung Won; Han, Dai Hoon; Lee, Yong-Ho; Bae, Soo Han
ABSTRACT: Lipotoxicity, induced by saturated fatty acid (SFA)-mediated cell death, plays an important role in the pathogenesis of nonalcoholic fatty liver disease (NAFLD). The KEAP1 (kelch like ECH associated protein 1)-NFE2L2/NRF2 (nuclear factor, erythroid 2 like 2) pathway is a pivotal defense mechanism against lipotoxicity. We previously reported that SQSTM1/p62 has a cytoprotective role against lipotoxicity through activation of the noncanonical KEAP1- NFE2L2 pathway in hepatocytes. However, the underlying mechanisms and physiological relevance of this pathway have not been clearly defined. Here, we demonstrate that NFE2L2-mediated induction of SQSTM1 activates the noncanonical KEAP1-NFE2L2 pathway under lipotoxic conditions. Furthermore, we identified that SQSTM1 induces ULK1 (unc-51 like autophagy activating kinase 1) phosphorylation by facilitating the interaction between AMPK (AMP-activated protein kinase) and ULK1, leading to macroautophagy/autophagy induction, followed by KEAP1 degradation and NFE2L2 activation. Accordingly, the activity of this SQSTM1-mediated noncanonical KEAP1-NFE2L2 pathway conferred hepatoprotection against lipotoxicity in the livers of conventional sqstm1 - and liver-specific sqstm1 -knockout mice. Moreover, this pathway activity was evident in the livers of patients with nonalcoholic fatty liver. This axis could thus represent a novel target for NAFLD treatment. Abbreviations: ACACA: acetyl-CoA carboxylase alpha; ACTB: actin beta; BafA1: bafilomycin A1 ; CM-H2DCFDA:5-(and-6)-chloromethyl-2ʹ, 7ʹ-dichlorodihydrofluorescein diacetate; CQ: chloroquine; CUL3: cullin 3; DMSO: dimethyl sulfoxide; FASN: fatty acid synthase; GSTA1: glutathione S-transferase A1; HA: hemagglutinin; Hepa1c1c7: mouse hepatoma cells; HMOX1/HO-1: heme oxygenase 1; KEAP1: kelch like ECH associated protein 1; MAP1LC3B/LC3B: microtubule-associated protein 1 light chain 3; MEF: mouse embryonic fibroblast; MTORC1: mechanistic target of rapamycin kinase complex 1; MTT: 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide; NAC: N-acetyl-L-cysteine; NAFLD: nonalcoholic fatty liver disease; NASH: nonalcoholic steatohepatitis; NFE2L2/NRF2: nuclear factor, erythroid 2 like 2; NQO1: NAD(P)H quinone dehydrogenase 1; PA: palmitic acid; PARP: poly (ADP-ribose) polymerase 1; PRKAA1/2: protein kinase AMP-activated catalytic subunits alpha1/2; RBX1: ring-box 1; ROS: reactive oxygen species; SESN2: sestrin 2; SFA: saturated fatty acid; siRNA: small interfering RNA; SQSTM1/p62: sequestosome 1; SREBF1: sterol regulatory element binding transcription factor 1; TBK1: TANK binding kinase 1; TUNEL: terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling; ULK1: unc-51 like autophagy activating kinase.